Molecular characterization of infectious laryngotracheitis virus (ILTV) isolates from outbreak cases at Lipa City, Batangas Province, The Philippines - Muharam Saepulloh (Jurnal Ilmu Ternak dan Veteriner, 2004)
Investigations were carried out to identify molecular character of infectious laryngotracheitis virus (ILTV) isolates from commercial layer chicken farm located at Lipa City, Batangas Province, the Philippines using western blotting. The virus was first isolated in chorio allantoic membrane (CAM). A-total of five isolates (#IV, #VI-C28, #VI-C29, #VI-C30, and #VII) produced typical plaque lesions in CAM at second passages such as yellowish plaques with opaque edges. Furthermore, five isolates were then characterized by western blotting on 7.5% of acrylamide. These results showed that Chicken antisera to the ILTV strain NS-175 (as standard sera), and rabbit antisera to vaccine strain (BAL-ILT) recognized four major viral protein with molecular weight of 205, 160, 85 and 60 kDa of isolates #VI-C28, #VI-C29, #VI-30 and #VII. While the isolate # IV produced viral protein of 205 and 85 kDa. The same four viral proteins were recognized by both ILTV antisera, indicating that the viral proteins of the vaccine strain and ILTV local isolates from Lipa City, Batangas Province, the Philippine had cross-reactivity. Thus, this cross reactivity may cause the effective protection afforded by the vaccine strain in the field.   Key words: Infectious laryngotracheitis virus, CAM, western blotting, chicken